Recent Marxian theory : class formation and social conflict in contemporary capitalism - Sitton, John F. (Albany : State University of New York Press, 1996)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: sociale klassen; proletariaat; sociale conflicten